2014
DOI: 10.1590/1519-6984.03513
|View full text |Cite
|
Sign up to set email alerts
|

Toxic concentrations of metronidazole to Microcystis protocystis

Abstract: Antimicrobials are among the most commonly used drugs and have become a class of contaminants with great environmental importance. Metronidazole is an antimicrobial used for the therapeutic management of several human diseases. The toxicity of antimicrobials on aquatic species may affect sensitive microorganisms and reduce metabolic processes. Cyanobacteria is a group of organisms that are of great ecological importance in aquatic environments. Studies indicate that cyanobacteria are very sensitive to some ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Till now, this species was reported as a true element of plankton in karst environments of the Yucatán peninsula, Mexico (López-Adrián & Barrientos-Medina, 2007;Tavera et al, 2013) which are rich in tropical species of cyanobacteria. This species was also reported on several localities in Brazil: in São Paulo State (Sant'Anna et al, 2004), in the Cordeiro, Camalau and Acauã Reservoirs (Vasconcelos et al, 2013) and in Minas Gerais State (Magalhães et al, 2014). It was also found in the neo-tropical, eutrophic reservoir Riogrande II in Colombia (Palacio et al, 2015), but still, up to our knowledge, it was never reported for Europe.…”
Section: Discussionsupporting
confidence: 54%
“…Till now, this species was reported as a true element of plankton in karst environments of the Yucatán peninsula, Mexico (López-Adrián & Barrientos-Medina, 2007;Tavera et al, 2013) which are rich in tropical species of cyanobacteria. This species was also reported on several localities in Brazil: in São Paulo State (Sant'Anna et al, 2004), in the Cordeiro, Camalau and Acauã Reservoirs (Vasconcelos et al, 2013) and in Minas Gerais State (Magalhães et al, 2014). It was also found in the neo-tropical, eutrophic reservoir Riogrande II in Colombia (Palacio et al, 2015), but still, up to our knowledge, it was never reported for Europe.…”
Section: Discussionsupporting
confidence: 54%
“…For Desmodesmus / Scenedesmus strains, metronidazole (within 7.8–125 μg/L) caused 50% inhibition of photosynthetic activity in Desmodesmus subspicatus culture [83], but in another study, at 705 mg/L, caused 50% inhibition to Scenedesmus vacuolatus [50]. For the cyanobacterium Microcystis protocystis , high resistance (50% inhibition at 117 mg/L) to metronidazole was reported [124].…”
Section: Inhibitory Effect Of Pharmaceuticals and Personal Care Prmentioning
confidence: 99%
“…Unfortunately, beyond high efficiency and high solubility in water, this drug is characterized by low biodegradability, high toxicity and the high ability to bioaccumulate in water. In addition, it was found that this substance is mutagenic and carcinogenic (Ocampo-Perez et al 2013;Magalhães et al 2014). Therefore, it is not surprising that many efforts are directed to remove the contamination of metronidazole from the aqueous environment.…”
Section: Resultsmentioning
confidence: 99%